On the use of MCDM technique for identifying key technology: a case of auto company - Mazlomi, Aliakbar; Mohd Yusuff, Rosnah (Engg Journals Publications, 2011)
In today's world, technology strategy development for industries is one of the most important tasks in proposing technology roadmap. Moreover, identifying strategic technology is main part of strategy development. This article tries to apply MCDM methods in finding key strategic technologies from identified technologies from in order to provide appropriate technology strategy. TOPSIS method helps in finding key strategic technologies from identified technologies from in order to provide appropriate technology strategy. At last Efficient TOPSIS method used for determining key strategic technology in Auto Company and key technology are derived from identified technology so as to develop technology strategy.